Effect of temporal randomization on the interaction of normalized and anomalous transport - Stanislavsky, A.A. (Вопросы атомной науки и техники, 2007)
The fractional kinetic equations are a natural consequence of non-Gaussian properties in the behavior of many complex systems. We consider the competition between normalized and anomalous transport in the presence of temporal subordination. The anomalous transport is induced by fractional spatial derivatives as occurs in fractional kinetic theory. It is shown that for large time the power tails of the probability density play a dominant role. This supports and extends the Weitzner-Zaslavsky's result obtained in a simpler case.